2022
DOI: 10.15420/aer.2022.11.s1
|View full text |Cite
|
Sign up to set email alerts
|

The ATLAS Randomised Clinical Trial: What do the Superiority Results Mean for Subcutaneous ICD Therapy and Sudden Cardiac Death Prevention as a Whole?

Abstract: This review sets out the key evidence comparing subcutaneous ICDs (S-ICDs) and transvenous ICDs and uses it to empower clinical cardiologists and those who implant ICDs to make optimum patient selections for S-ICD use. The evidence demonstrates that clinical trials performed until recently have proven the performance of S-ICDs. However, the latest data now available from the ATLAS randomised controlled trial have added new insights to this body of evidence. ATLAS demonstrates the superiority of S-ICDs over tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The S‐ICD offers the advantage of obviating the need for a lead that crosses the TV, therefore eliminating lead‐valve interactions that may lead to TR. The benefit of S‐ICD in mitigating risk of TR was empirically demonstrated in the ATLAS (Avoid Transvenous Leads in Appropriate Subjects) trial, 52 where the incidence of new‐onset moderate‐severe or severe TR following ICD implantation was lower in patients who underwent S‐ICD placement as compared to those patients receiving a standard transvenous device (0% vs. 1.2%, odds ratio 0.26, 95% confidence interval: 0.0–1.72, p = .13).…”
Section: Mechanisms Of Cied‐induced Trmentioning
confidence: 99%
“…The S‐ICD offers the advantage of obviating the need for a lead that crosses the TV, therefore eliminating lead‐valve interactions that may lead to TR. The benefit of S‐ICD in mitigating risk of TR was empirically demonstrated in the ATLAS (Avoid Transvenous Leads in Appropriate Subjects) trial, 52 where the incidence of new‐onset moderate‐severe or severe TR following ICD implantation was lower in patients who underwent S‐ICD placement as compared to those patients receiving a standard transvenous device (0% vs. 1.2%, odds ratio 0.26, 95% confidence interval: 0.0–1.72, p = .13).…”
Section: Mechanisms Of Cied‐induced Trmentioning
confidence: 99%
“…A recent meta-analysis of 13 studies, comprising 9073 patients, demonstrated that S-ICDs are at least as effective and safe as TV-ICD for preventing sudden cardia death in patients without an indication for pacing [ 158 ]. The ATLAS trial [ 159 ] was the first superiority trial and demonstrated a 92% reduction in lead-related complications for S-ICDs compared with TV-ICDs at 6 months. In spite of this, the inherent limitations for S-ICDs remain, namely, bradycardia pacing, cardiac resynchronization and ATP.…”
Section: Icd Cost Reductionmentioning
confidence: 99%
“…The occurrence of lead-related complications was significantly higher in TV-ICD patients (6.6% in the TV-ICD arm versus 1.4% in the S-ICD arm; p = 0.001) [ 11 ]. The ATLAS trial reported 4.8% lead complications in the TV-ICD group compared to 0.6% in the S-ICD group at six months [ 12 ].…”
Section: Subcutaneous Icd: What We Know So Farmentioning
confidence: 99%
“…Indeed, transvenous lead-related complications are reported to be very high in this population and have been linked to a relevant risk of IASs [ 66 ]. In the ATLAS trial, which enrolled younger patients compared to other studies, a lower rate of major lead-related complication in S-ICD patients was noted [ 12 ]. Although there might be a mismatch between the size of the generator case compared to the available anatomical location in the lateral axilla in infants and small children, subcutaneous leads are better suited to body growth changes and therefore more adaptable for young people who are still growing.…”
Section: Indications For S-icd Implantmentioning
confidence: 99%
See 1 more Smart Citation